Catalogue of the Byzantine coins in the Dumbarton Oaks Collection and in the Whittemore Collection. Vol. V : Michael VIII to Constantine XI, 1258-1453. Pt. 2 : catalogue, concordances, and indexes (Washington)
x, s. [289]-611, 91 s. res.